Multiple molecular dynamics simulations of human LOX‐1 and Trp150Ala mutant reveal the structural determinants causing the full deactivation of the receptor. Issue 10 (12th July 2017) - Iacovelli, Federico; Tucci, Fabio Giovanni; Macari, Gabriele; Falconi, Mattia
Abstract: Multiple classical molecular dynamics simulations have been applied to the human LOX‐1 receptor to clarify the role of the Trp150Ala mutation in the loss of binding activity. Results indicate that the substitution of this crucial residue, located at the dimer interface, markedly disrupts the wild‐type receptor dynamics. The mutation causes an irreversible rearrangement of the subunits interaction pattern that in the wild‐type protein allows the maintaining of a specific symmetrical motion of the monomers. The subunits dislocation determines a loss of linearity of the arginines residues composing the basic spine and a consequent alteration of the long‐range electrostatic attraction of the substrate. Moreover, the anomalous subunits arrangement observed in the mutated receptor also affects the integrity of the hydrophobic tunnel, actively involved in the short‐range hydrophobic recognition of the substrate. The combined effect of these structural rearrangements generates the impairing of the receptor function.